A Decade and a Half of Day Care Service for Persons with Psychiatric Disabilities: The RFS (I) Experience - Sahu, Kamlesh Kumar (International Journal of Psychosocial Rehabilitation, 2014)
Background: Day care is a cost-effective service offering daytime care and support to persons with psychiatric and intellectual disabilities. It is effective in building users’ self-esteem and in improving their social functioning and community integration. It is also effective in reducing caregiver’s burden. Objective: To appraise the services provided by the ‘Chetana’ Day Care Centre with Vocational training run by the Richmond Fellowship Society (India), Bangalore. Materials and Methods: A retrospective approach was adopted. Individual case files of 228 users who were formally admitted into the centre over last 15 years were reviewed to identify benefits to them due to attending the centre. Routine entries made by professional staff in the case record files, other periodical reports, staff assessment reports of users, and feedbacks from users and families were used to identify the benefits derived. Conclusion: The users and their families reported widespread benefits that have accrued either directly or indirectly by being in the day care programme. Staff feedback about the programme performance was also identified. Important areas of learning and challenges were derived from the 15-year experience of offering day care rehabilitation services for persons with psychiatric and intellectual disabilities.